A secure new HRF mechanism for mitigate EDoS attacks. (14th June 2022) - Bulla, Suneetha; Basaveswararao, B.; Rao, K. Gangadhara; Chandan, K.; Swamy, Sirisati Ranga
This paper proposes HTTP request filtering (HRF) mechanism to detect and mitigate EDoS attacks and compare the performance with existing mechanism through game theoretical approach. The HRF mechanism was implemented with three stages and hosted on web application firewalls (WAF). The performance of these mechanisms with cost analysis is done using finite queuing model. The efficiencies are compared with the formation of two player non-cooperative zero-sum game and gains are calculated based on loss probability as a QoS metric. To obtain the analytical solution and computation of game value, different probabilities of defending strategies and attacking strategies through numerical illustrations are carried out. The results are discussed and finally conclusions are drawn.